Green Synthesis Of Silver Nanoparticles Using Leaves Of Lepisanthes Tetraphylla And Evaluation Of Their Antibacterial Activity Against Drug Resistant Clinical Isolates - N.MEENA; M.JEYA; S.AROUMUGAME; P.ARUMUGAM; E.SAGADEVAN (International Journal of Pharma and Bio Sciences, 2012)
The silver nanoparticles (AgNPs) synthesized using aqueous leaf extract of Lepisanthes tetraphylla as the reducing agent were evaluated for antibacterial activity against drug resistant bacterial isolates. The nature of AgNPs synthesized were analysed by UV-Vis spectroscopy, X-ray diffraction and Scanning electron microscopy. The silver nanoparticles were with an average size of 30nm, spherical and poly-dispersed. The antibacterial potential of synthesized AgNPs were compared with that of crude methanolic leaf extract of Lepisanthes tetraphylla by well diffusion method. The AgNPs at 30-50µg(0.03-0.05mg) concentration significantly inhibited bacterial growth against multi drug resistant Staphylococcus aureus , Escherichia coli, Pseudomonas aeruginosa and Acinetobacter species. The study revealed that crude methanolic leaf extract of L.tetraphylla inhibited the growth of only Escherichia coli, at 1mg/ml concentration. Thus AgNPs showed broad spectrum antibacterial activity at lower concentration may be a good alternative therapeutic approach in future.